2019
DOI: 10.17222/mit.2019.068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium-permanganate modification on the microstructure and adsorption property of activated carbon

Abstract: Potassium permanganate was loaded onto activated carbon using the impregnation method to obtain modified activated carbon. The activated carbon and activated carbon loaded with potassium permanganate were then placed in a closed, newly decorated house. It was found that formaldehyde amount decreased sharply after the adsorption of the activated carbon, and further decreased after the adsorption of the activated carbon modified with potassium permanganate. By measuring the amount of formaldehyde in the room bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…According to Wu et al 2019, the loading of potassium permanganate onto the activated carbon did not change the lattice structure of the carbon. The higher crystallinity on activated carbon with KMnO4 was because the distance of aromatic structure (d) decreased along with narrowing the width of aromatic structure.…”
Section: Intensity (Counts)mentioning
confidence: 99%
“…According to Wu et al 2019, the loading of potassium permanganate onto the activated carbon did not change the lattice structure of the carbon. The higher crystallinity on activated carbon with KMnO4 was because the distance of aromatic structure (d) decreased along with narrowing the width of aromatic structure.…”
Section: Intensity (Counts)mentioning
confidence: 99%
“…The TEM images depicted that particles were arranged randomly and overlapping one another. The particles of carbonized carbons appeared relatively round, whereas in AC the particles displayed rough and uneven shapes . The structure was amorphous because of the randomly arranged particles and a rough and uneven shape.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The particles of carbonized carbons appeared relatively round, whereas in AC the particles displayed rough and uneven shapes. 67 The structure was amorphous because of the randomly arranged particles and a rough and uneven shape. The graph of carbonized carbon (a 2 ) showed that most particles were found in the range of 21 to 60 nm.…”
Section: Resultsmentioning
confidence: 99%
“…KOH is a potent alkaline activating agent [9]. KOH is the most effective activating agent for preparing AC with an extremely high specific surface area.…”
Section: Introductionmentioning
confidence: 99%